Container Terminals and Automated Transport Systems Logistics Control Issues and Quantitative Decision Support - Günther, Hans-Otto; Kim, Kap Hwan (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Container transportation is the predominant mode of inter-continental cargo traffic. Since container ships and port terminals involve a huge capital investment and significant daily operating costs, it is of crucial importance to efficiently utilize the internal resources of container terminals and transportation systems. Today there is an ongoing trend to use automated container handling and transportation technology, in particular, in countries with high labour costs. This in turn requires highly sophisticated control strategies in order to meet the desired performance measures. The primary objective of this book is to reflect these recent developments and to present new insights and successful solutions to operational problems of automated container terminals and transportation systems. It comprises reports on the state of the art, applications of quantitative methods, as well as case studies and simulation results. Its contributions are written by leading experts from academia and business. The book addresses practitioners as well as academic researchers in logistics, transportation, and management.